Toxic Effect and Molecular Mechanism of Arsenolipids on Promoting Aging in Caenorhabditis elegans - YIN Huan, SONG Bingbing, LI Ziyu, WANG Zhuo, ZHAO Qiaoli, LI Rui, CHEN Jianping, ZHONG Saiyi (Shipin Kexue)
In this study, we explored the effect of two arsenolipids with different molecular masses, AsHC 332 and AsHC 346, which are commonly found in seafood, on aging and lifespan-related indicators in the model organism Caenorhabditis elegans. The possible mechanism by which the arsenolipids promote aging was analyzed by measuring the expression of DAF-16 protein in the nematode, the longevity of aging mutants and stress-related genes. The results showed that AsHCs significantly reduced the body length, body width, brood size and head thrash frequency of C. elegans in a dose-dependent manner (P < 0.05). Moreover, the resistance to heat stress (P < 0.000 1) and ultraviolet stress (P < 0.05) was significantly reduced by AsHCs. The lifespan of C. elegans was significantly shortened (P < 0.01). The accumulation of lipofuscin was increased (P < 0.001). The relative expression of the daf-16, sod-3, ctl-1, gst-4 and hsp-16.2 genes was up-regulated, while the nuclear localization of DAF-16 was not significantly promoted, and there was no effect on the lifespan of the daf-16(mu86) mutant. AsHC 332 and AsHC 346 had the same toxic effects on nematode aging, which may shorten the lifespan of C. elegans by regulating the transcription factor DAF-16.